Bibliometric Analysis of Research on Financial Technology (FinTech) in the ASEAN Region: Research Streams, Influential Works, and Future Research Paths - Wahdaniyah, Nurul; Nurmandi, Achmad; Younus, Muhammad (Jurnal Siasat Bisnis, 2026)
Purpose – This paper aims to identify trends and research mapping of financial technology (FinTech) in the ASEAN Region that have been of interest to academics and practitioners through the help of Vosviewers' application in visualizing the data. Design/methodology/approach – The method used in this research is qualitative research with a literature study approach. The data found were 88 documents and then analyzed. This dataset was converted to CSV format, imported into Bibliometrix, and analyzed. Findings – This study revealed a significant increase in research on Financial Technology from 2019 to 2023, indicating a growing interest among academics. Key terms such as Finance, Financial Inclusion, Banking, Financial Services, Financial Markets, Financial Services, Financial System, Innovation, Technology Adoption, Governance, and Technology Development were the most frequently used. These concepts are crucial in understanding the impact of Financial Technology on various economic and social aspects. This research highlights the relevance of Financial Technology not only for enhancing financial inclusion but also for public policy, financial stability, and the development of the digital economy globally. Supporting research and development in this area is therefore crucial. Research limitations/implications – The main limitation of the research should be the use of data only from the Scopus database. Practical implications – This paper guides academics and practitioners in understanding the key trends and focus of FinTech research. The results also help support FinTech policy development and innovation in the ASEAN region. Originality/value – This paper reveals the research trends and areas of Financial Technology. The results help scholars quickly understand Financial Technology research. The paper also provides an alternative approach to conducting literature reviews with computer-aided analysis programs. Keywords: Financial Technology, Technology Adoption, Innovation and Technology Development.